KARAKTERISASI BAKTERI LIPOLITIK Bacillus sp. PADA WADI ORGAN PENCERNAAN IKAN SIDAT (Anguilla sp.): Characterization of Lipolitic Bacteria Bacillus sp. in Wadi of Digestive Organs of Sidat Fish (Anguilla sp.) - Vicky Mahendra Nurzhulian; Ayu Rahmawati Sulistyaningtyas; Stalis Norma Ethica (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2022)
ABSTRACT One of the leading enzymes having the potential to donate profit of billions of dollars in food and health sector is lipase. Lipase can be produced from microorganisms including bacteria. Lipolytic bacteria can be found in the digestive tract of fish. This study aims to obtain lipolytic bacteria ifrom the wadi fermentation products of digestive organs of Sidat Fish (Anguilla sp.) and to identify bacterial species based on the 16S rRNA gene sequence. Samples of wadi fermentation products of fish digestive organs were serially diluted and cultured on Nutrient Agar (NA). The purified bacterial isolates were microscopically identified and tested for their lipolytic activity using Tween-80 agar media. Bacterial isolates with the highest lipolytic index were subjected to bacterial identification based on the 16S rRNA gene using the Polymerase Chain Reaction (PCR) method. The results showed that from the prepared wadi samples, five bacterial isolates coded WFAD-1 to WFAD-5 (WFAD stands for Wadi Fermentation of Anguilla sp. Digestive organs) could be obtained. Of these 5 isolates, two of them, WFAD-1 and WFAD-3, were capable of producing lipase and in particular, WFAD-1 had the highest lipolytic index of 2.95. BLAST analysis result on the amplified 16S rRNA gene of WFAD-1 isolate revealed a similarity level 85.79% and query coverage of 61% with Bacillus velezensis. Based on microscopic and molecular identification results, the lipolytic isolate WFAD-1 can be categorized into the genus Bacillus. As conclusion, Bacillus sp. WFAD-1 isolated from wadi fermentation product of digestive organs of ikan sidat has a potential as a source of bacterial lipase. ABSTRAK Salah satu enzim utama berpotensi menyumbang keuntungan miliaran rupiah di bidang pangan dan kesehatan adalah lipase. Lipase dapat dihasilkan dari mikroorganisme termasuk bakteri. Bakteri lipolitik dapat ditemukan di saluran pencernaan ikan. Penelitian ini bertujuan untuk mendapatkan bakteri lipolitik pada produk fermentasi wadi organ pencernaan ikan Sidat (Anguilla sp.) dan mengidentifikasi spesies bakteri tersebut berdasarkan urutan gen 16S rRNA. Sampel hasil fermentasi wadi organ pencernaan sidat diencerkan bertingkat lalu dikultur pada media Nutrient Agar (NA). Isolat bakteri yang telah dimurnikan diidentifikasi secara mikroskopis dan diuji aktivitas lipolitiknya menggunakan media agar Tween-80. Isolat bakteri dengan indeks lipolitik tertinggi diidentifikasi berdasarkan gen 16S rRNA dengan metode Polymerase Chain Reaction (PCR). Hasil penelitian menunjukkan bahwa dari sampel wadi yang telah dibuat, dapat diperoleh lima isolat bakteri yang diberi kode WFAD-1 hingga WFAD-5 (WFAD singkatan dari Wadi Fermentation of Anguilla sp. Digestive organ). Dari 5 isolat tersebut, dua di antaranya yaitu WFAD-1 dan WFAD-3 mampu menghasilkan lipase dan khususnya WFAD-1 memiliki indeks lipolitik tertinggi yaitu 2,95. Hasil analisis BLAST pada produk amplifikasi gen 16S rRNA isolat WFAD-1 menunjukkan tingkat kemiripan 85,79% dan cakupan query 61% dengan Bacillus velezensis. Berdasarkan hasil identifikasi mikroskopis dan molekuler, WFAD-1 lipolitik dapat dikategorikan dalam genus Bacillus. Sebagai kesimpulan, Bacillus sp. WFAD-1 yang diisolasi dari produk fermentasi wadi organ pencernaan ikan sidat berpotensi sebagai sumber lipase bakterial.